White book of Viet Nam information and communication technology 2017 : Information and statistical data (H. Information and Communications publising house, 2017)
The White Book 2017 provides official statistical data and information on a number of areas managed by the Ministry, namely: information technology application, information technology industry, information security, telecommunications, internet,....
Keywords: Công nghệ thông tin